Varicocele in Men: The Problem of Male Infertility (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Demographic problems in Uzbekistan require paying more attention to reproductive health of adolescents. WHO reports 50% contribution of male factor in infertile couples. Among the reasons causing male infertility varicocele can be emphasized. Numerous of long-term researches are dedicated to male infertility in adults. Far less researches of varicocele in kids and adolescents can be found. That could be connected with particularity of diagnostic and treatment. Varicocele influence on spermatogenesis and surgery efficiency are still discussed and researched. Materials and methods. 500 patients with varicocele underwent surgery for last 5 years in BRMMC of Urology. Diagnosis was based on physical examination, ultrasound and Doppler investigation. Left-sided varicocele was in 89% of cases, right-sided in 1%, two-sided in 10%. Spermatogenesis status was determined due to WHO recommendations. In a group of 200 adolescents after parental permission ejaculate analyses was taken. Age varied from 16 to 18. Statistic analyses was used. Results. Mean level of main ejaculate characteristics was lower than normally. After the surgery sperm cells concentration increased meanly from 35 to 61 mln/ml, quantity of alive cells meanly increased from 70% to 77%. “A” category sperm cells improved meanly from 20% to 50%.Conclusions. Varicocele affects spermatogenesis, can lead to infertility. In adults, significant changes in spermatogenesis in most cases, surgery gives positive results.